A PREDICTION MODEL OF COMPANY HEALTH USING BAGGING CLASSIFIER (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
In business, have many competitions between companies occur to obtain as many profits as possible, Financial Distress is a financial decline that occurs in companies, reflecting the health of the company before bankruptcy started. Therefore, to avoid bankruptcy, it requires a method or tool with high accuracy in identifying company health. This research uses a bagging classifier, which is one type of Ensemble Learning algorithm. To predict financial difficulties, the authors use the bagging classifier algorithm with 0.13% more accurate results than previous studies using the XGBoost algorithm.
Keywords: financial distress; bagging classifier; XGBoost